A Visual Identity-Based Approach of Southeast Asian City Branding: A Netnography Analysis - Bahtiar Mohamad; Raji Ridwan Adetunji; Ghadah Alarifi; Ahmed Rageh Ismail; Muslim Diekola Akanmu (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2022)
Cities and places had been progressively being marketed as brands by using the concept of ‘City Branding', which is a unique idea. The scholars of ‘City Branding’ believed that the concept of branding helps the city in marketing activities. A city metaphorically could be seen as an entity given the advantage to display its visual characteristics to tourists, visitors, and residents. Unique visual identity such as iconic architecture and graphic design could make a city stands out from the others. Thus, the research examined the role of visual identity in city branding. Specifically, the aim was to contribute to better understanding of the concept of ‘visual identity’ in Southeast Asian cities. Netnography approach was employed to gain better understanding of the notion of visual identity of city branding and refine a conceptual framework that has been developed based on the existing literature. Elements such as iconic structure and graphic design (logo and slogan) of four cities in Southeastern Asia were emphasized. The research concludes that the components of the visual identity of the cities need to be reshaped to be aligned with their visual characteristics in order to boost their competitiveness among the global city brands.